2007
DOI: 10.1002/pssc.200675816
|View full text |Cite
|
Sign up to set email alerts
|

Digital positron lifetime spectrometer for measurements of radioactive materials

Abstract: A digital positron lifetime spectrometer for the measurements of 2 GBq level radioactive materials has been constructed and successfully tested. The equipment consists of a state-of-the-art digital oscilloscope and three movable scintillation detectors operating in triple-coincidence mode. The time resolution of 188 ps full-width at half-maximum (FWHM) is achieved for the positron lifetime measurements of radioactive specimens. Also by comparison of measurements of well-known material with and without high 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The resolution of the setup was constantly checked to be about 175 ps, while the source contribution was set to 15% with a single lifetime of 393 ps. More detailed information about the experimental setup is given in [23,25]. All measurements were performed at room temperature using a 22 Na positron source, with a strength of 2 MBq, wrapped in Kapton foils.…”
Section: Positron Lifetime Measurementsmentioning
confidence: 99%
“…The resolution of the setup was constantly checked to be about 175 ps, while the source contribution was set to 15% with a single lifetime of 393 ps. More detailed information about the experimental setup is given in [23,25]. All measurements were performed at room temperature using a 22 Na positron source, with a strength of 2 MBq, wrapped in Kapton foils.…”
Section: Positron Lifetime Measurementsmentioning
confidence: 99%
“…Time resolution is considered as one of the key parameters to evaluate the characteristics of a PAL spectrometer. Numerous efforts have been made to improve the time resolution of PAL spectrometers over the past twenty years [15][16][17][18][19][20][21][22][23][24][25][26]. The tendency is to develop digital PAL spectrometers in which analog electric modules are substituted by fast digitizers.…”
Section: Introductionmentioning
confidence: 99%
“…The main lifetime used within this paper has been measured, but it is very close to the calculated value (s m = I 1 Â s 1 + I 2 Â s 2 ). More detailed information about the experimental setup is given by Jardin et al [18,20]. Here, it has been shown that for our setup, the lifetime measured in non-irradiated pure Fe samples corresponds to (107.57 ± 0.38) ps.…”
Section: Positron Lifetime Measurementsmentioning
confidence: 91%